2002
DOI: 10.1038/labinvest.3780443
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Dipeptidyl Peptidase IV in Immune Complex–Mediated Glomerulonephritis

Abstract: SUMMARY:Dipeptidyl peptidase IV (DPPIV) is widely expressed in many tissues; however, its precise biological function is poorly understood. One of its possible physiologic roles is an involvement in the immune system, which plays a pivotal role in the pathogenesis of glomerulonephritis. The present study focused on the involvement of DPPIV in immune complex-mediated glomerulonephritis. Experimental nephritis was induced by anti-Thy-1.1 monoclonal antibody E30 using Wistar or F344 rats. The application of a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Shinosaki et al (30) previously reported that monoclonal antibody against DPP-4 considerably reduced proteinuria and mesangial expansion via the suppression of the complement cascade in the rat Thy-1 model. Contrary to this report, we observed a nonsignificant trend toward reductions in glomerular injury and proteinuria in the present study.…”
Section: Discussionmentioning
confidence: 98%
“…Shinosaki et al (30) previously reported that monoclonal antibody against DPP-4 considerably reduced proteinuria and mesangial expansion via the suppression of the complement cascade in the rat Thy-1 model. Contrary to this report, we observed a nonsignificant trend toward reductions in glomerular injury and proteinuria in the present study.…”
Section: Discussionmentioning
confidence: 98%
“…11 HMGB1, a nuclear protein that regulates gene transcription, is passively released after cell injury and has been implicated in tissue inflammation in animal models of kidney injury. 13,30 HMGB1 is a known ligand of TLR, which leads to the activation of NF-kB, ultimately increasing tissue inflammation. 12,31 We also found that renal expression of HMGB1 was decreased in mice given LC15-0444 treatment in this study.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest a protective role for the neutralizing antibody of DPP-4 against complement-mediated tissue injury. 68 However, it is unclear whether similar modes of protection might be conferred by the enzymatic inhibition of DPP-4 using DPP-4 inhibitors and whether GLP-1 phenocopies these immune-modulating effects.…”
Section: Nondiabetic Chronic Kidney Diseasementioning
confidence: 99%